The diagnostic and treatment challenges of a primary breast angiosarcoma: a rare case report - Walisinghe, Lithira R.; Thompson, Callum P.; Kasem, Kais; Gu, Ji (International Surgery Journal, 2025)
Primary angiosarcoma of the breast (PAB) is an aggressive malignancy that represents less than 0.05% of breast malignancies. PABs can pose a diagnostic challenge as they present in the absence of risk factors and in younger patients where breast density weakens the diagnostic utility of imaging. Treatment decisions may also be challenging as there remains scant consensus on the most appropriate mix of surgical and adjuvant treatment modalities. We report the case of a 40-year-old female who presented with a 1-centimeter peri-areolar nodule. After initial suspicion for infection and failure of anti-microbial therapy, a shave biopsy was performed. Angiosarcoma was subsequently confirmed and further wide local excision demonstrated no residual disease, likewise imaging was also not concerning for metastases. Given reassuring clinical progress, consensus among the multidisciplinary team was for surveillance without adjuvant therapy. The case was fortunate to have early cutaneous manifestation, and thus lead to earlier presentation, intervention and a positive outcome. Nonetheless it demonstrates the potential challenges to diagnosis in young patients who present with an absence of risk factors, and the case-by-case deliberation regarding management. Clinicians should remain vigilant of atypical, indeterminate breast lesions and ensure progression to more sensitive imaging and prompt biopsy to prevent missed or delayed diagnoses. A diagnosis of primary breast angiosarcoma should have early expert involvement, aggressive intervention and thorough follow up to optimise patient outcome.